Strategi Guru dalam Mengatasi Kesalahan Penulisan Ejaan pada Siswa Kelas Rendah SD - Salwa Sa'diyyah; Iva Sarifah; Mahmud Yunus (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
T This study aims to describe the strategies used by teachers in overcoming spelling errors in low-grade elementary school students. Spelling problems are one of the common difficulties for low-grade students, such as errors in the use of capital letters, punctuation marks, spacing between words, and the writing of absorbed elements. This study used a descriptive method with data collection techniques in the form of interviews, observations, and documentation of low-grade teachers in several elementary schools. Data analysis was conducted through the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that spelling errors that often occur include: improper placement of capital letters, inconsistent spacing, incorrect use of punctuation marks, and word writing errors. To overcome these problems, teachers apply several strategies, such as providing additional study time, giving more attention to students who are having difficulty, correcting errors directly with feedback, and collaborating with parents to accompany children when studying at home. This study emphasizes the importance of teachers' active role and parents' support in improving students' basic literacy skills early on, so that errors in writing do not become sustainable habits at the next level of education.